Psychometric Examination of Treatment Change Among Mentally Disordered Offenders: A Risk–Needs Analysis - Kingston, Drew A. (Criminal justice and behavior, 2018)
The present study examined the association of psychiatric symptomatology, criminal attitudes, and treatment changes within these domains to violent and general recidivism in a sample of 614 mentally disordered offenders. Significant pre-post changes were found on multiple measures of criminal attitudes, symptomatology, and readiness for change. Antisocial Intentions and Attitudes Toward Associates (from the Measure of Criminal Attitudes and Associates [MCAA]) predicted general recidivism and covaried with the Big Four criminogenic need domains on the Level of Service Inventory-Ontario Revision; none of the remaining psychometric measures significantly predicted violent or general recidivism. Although pre-post changes were seldom linked to changes in recidivism, positive changes in Antisocial Intentions (MCAA) significantly predicted reductions in general recidivism via Cox regression survival analysis, controlling for baseline risk and pretreatment attitudes score. Risk and need implications of psychometric assessments of treatment change in mentally disordered offender populations are discussed.